An Inquisition for Propaganda and Mass Deception: Deposing the Neolithic Mind - Walsh, Robert L. (Frontiers in Communication, 2021)
Human language harbors a mechanical aberration, leaving human communication vulnerable to manipulation. Mass deception is the systematic exploitation of this linguistic glitch, the agency of which is premeditated indoctrination. Its influence over human thought and behavior is rooted in the phenomenon of the tribal mind, an unconscious collective ego predisposed to propaganda. In its early modern iterations, Eddie Bernays heralded propaganda as an efficient way to establish shared understanding between an individual and established information that this individual encounters. Communicating to the masses was seen as a means of educating the masses, and this was celebrated. Now, though, inside the utter profusion of multifaceted information, propaganda’s bearing in mass communication cannot be ignored as a contaminant at its source. The challenge is the ease with which intra-action can be subtly systematized, around an insidious fatal flaw.